Media and everyday life in modern society - Moores, Shaun (Edinburgh University Press, 2000)
What position have television, radio and other electronic media like telephones and computers come to occupy in people's day-to-day lives and social relationships?How do these communication and information technologies get used and made sense of in local settings such as the household and the urban neighbourhood?How have they helped to construct new arrangements of time, space and place in a culture with globalising tendencies?What types of identity, experience and interaction do the electronic media make available to their different audiences or users?In this accessibly written book, Shaun Moores offers a particular set of answers to these general questions for media and cultural studies, drawing on a range of his investigations and reflections on media and everyday life in modern society. Combining theory with empirical research, he engages with the ideas of key thinkers - such as Giddens, Goffman, Hall and Williams - whilst also referring to detailed ethnographic and historical data.